Surgical Management of Neuromas of the Hand and Wrist. Issue 10 (15th May 2019) - Regal, Steven; Tang, Peter
Abstract : Neuromas of the hand and wrist are common causes of peripheral nerve pain. Neuromas are formed after the nerve sustains an injury, and they can be debilitating and painful. The diagnosis is made by a thorough history and physical examination. The treatment options are quite varied, but conservative measures tailored to the patient should be initiated first. No surgical treatment has been proven superior to others or to nonsurgical treatment.